Late Quaternary climate variations in West Antarctica and their impact on the marine siliceous microalgae - A. P. Olshtynska; O. S. Ogienko (Ukrainian Antarctic Journal, 2017)
Main objective is the reconstruction of late Quaternary climatic events in the northern and north-western parts of the Antarctic Peninsula shelf based on species variation, abundance and ecological structure of diatom complex in bottom sediments. Methods: siliceous microalgae were used as biomarkers of geologycal, paleogeographycal and facial events. Results: the reasons for changing of the diatom composition in bottom sediments were determined; paleogeographic reconstraction and chronology of the Late Quarter paleoclimatic trends in the region were investigated. Conclusions of the main paleoclimatic events of the Late Quarter within the northwestern shelf and in the southern part of the Skotia Sea are made. Two climatic phases are identified: «Little Ice Age» (900-500 years ago) with moderate icy conditions and the next phase of rapid modern warming.